2019
DOI: 10.1371/journal.pone.0220903
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptor blocker losartan exacerbates muscle damage and exhibits weak blood pressure-lowering activity in a dysferlin-null model of Limb-Girdle muscular dystrophy type 2B

Abstract: There is no cure or beneficial management option for Limb-Girdle muscular dystrophy (MD) type 2B (LGMD2B). Losartan, a blood pressure (BP) lowering angiotensin II (AngII) receptor type 1 (ATR1) blocker (ARB) with unique anti-transforming growth factor-β (TGF-β) properties, can protect muscles in various types of MD such as Duchenne MD, suggesting a potential benefit for LGMD2B patients. Herein, we show in a mild, dysferlin-null mouse model of LGMD2B that losartan increased quadriceps muscle fibrosis (142%; P<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…A similar controversy has also surrounded other molecules related to muscle function that have been proposed as biomarkers for frailty such as myostatin [47][48][49][50][51], follistatin [48,[50][51][52], and renin-angiotensin system elements [53][54][55][56][57]. Some authors have proposed that myostatin may act as a chalone, by turns restraining skeletal muscle growth in response to unfavorable metabolic scenarios or decreasing its own activity, when there is no need to restrain growth [50,51,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar controversy has also surrounded other molecules related to muscle function that have been proposed as biomarkers for frailty such as myostatin [47][48][49][50][51], follistatin [48,[50][51][52], and renin-angiotensin system elements [53][54][55][56][57]. Some authors have proposed that myostatin may act as a chalone, by turns restraining skeletal muscle growth in response to unfavorable metabolic scenarios or decreasing its own activity, when there is no need to restrain growth [50,51,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Picca et al [68] have described a U-shaped association between mTOR and cognitive function along the aging process. Thus, it may be that the seemingly contradictory results regarding certain putative molecular biomarkers of frailty are due to the up-regulation of compensatory systems on the frail organism, resulting in a U-shaped association; that is, during aging process, the serum concentration of such molecules is affected in one sense (increasing or decreasing), but later, the organism's compensatory mechanisms provoke the opposite effects (decreasing or increasing, respectively) [47,48,[50][51][52][53][54][55][56][57]. This is merely a general hypothesis that must to be confirmed for each molecule proposed as a biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that FAP (fibroblast activation protein alpha) [205], EYA4 [206], BCL9 [207], IRF2BP2 [208], EGR3 [209], GADD45B [210], DMD (dystrophin) [211], LSR (lipolysis stimulated lipoprotein receptor) [212], DLL4 [213], SUN2 [214], SOS1 [215], PIK3CA [216], GAMT (guanidinoacetate N-methyltransferase) [217], RBM47 [218], HSP90AA1 [219], GAB1 [220], S1PR1 [221], EDNRB (endothelin receptor type B) [222], NFKBIA (NFKB inhibitor alpha) [223], GJA1 [224], GADD45G [225], PHLDA1 [226], CMPK2 [227], FIGN (fidgetin, microtubule severing factor) [228], KCNJ2 [229], ABCC9 [230], DIRAS3 [231], EPHX1 [232], RAB4A [233], UBIAD1 [234], CASQ2 [235], TTN (titin) [236], KCNH1 [237], JPH2 [238], OXGR1 [239], UCHL1 [240], SERPINA3 [241], MMP28 [242], ADAMTS2 [243], P2RY1 [244], CSF2RA [245], MYO1F [246], SELPLG (selectin P ligand) [247] and SAMHD1 [248] are expressed in cardiovascular disease, but these genes might be novel target for T1DM. MAOB (monoamine oxidase B) [249], VEGFC (vascular endothelial growth factor C) [250], DBP (D-box binding PAR bZIP transcription factor) [251], MYADM (myeloid associated differentiation marker) [252], NES (nestin) [253], SMURF1 [254], EDNRB (endothelin receptor type B) [255], MUC6 [256], TOR2A [257], TNKS (tankyrase) [258], NEDD9 [259], ASIC1 [260], ADAMTS8 [261], DYSF (dysferlin) [262], SLC26A9 [263], SLC45A3 [264] and KCNQ2 [265] contributes to the progression of hypertension, but these genes might be novel target for T1DM. Yang et al [266], Zhang et al [267] and Wang et al [268] demonstrated that SYVN1, BTG1 and CFB (complement factor B) were associated with diabetic retinopathy, but these genes mi...…”
Section: Discussionmentioning
confidence: 99%
“…Unfixed frozen hearts from WT mice treated with telmisartan for two weeks were homogenized in lysis buffer and centrifuged 16 . Following protein quantification, samples were resolved using SDS-PAGE and transferred onto nitrocellulose membrane.…”
Section: Methodsmentioning
confidence: 99%
“…However, whether ARBs have direct class effects on the vasodilatory properties of the endothelium has never been reported. We have shown that ARB losartan has retained its anti-aortic root widening effects in Marfan syndrome (MFS) mice with blunted AT1R receptor expression 15 , along with high levels of endothelial function activation during chronic losartan 16 and valsartan 17 treatment, highlighting the potential presence of AngII/AT1R-independent pleiotropic. In the present report, we show in mice that ARBs share the ability to increase endothelial function for months that far exceed that observed with angiotensin converting enzyme inhibitor (ACEi) captopril on a same BP-lowering level.…”
Section: Introductionmentioning
confidence: 99%